School Governance and Secondary School Performance in Ndorwa County Kabale District Uganda. - Kyomuhangi, Hope (Kabale University, 2025)
This study examined the relationship between school governance and staff performance in secondary schools in Ndorwa East County, Kabale District. It focuses on four key objectives: (i) assessing the levels of school governance established in these schools, (ii) determining the relationship between governance levels and staff performance, (iii) identifying challenges affecting governance and staff performance, and (iv) proposing reforms to enhance staff performance. The findings aim to provide actionable insights for improving governance practices and educational outcomes in the region.